Contextual Interpretation and the Existence of Women and Their Implications for Equalization of the Inheritance of Men and Women - Muhammad Mahsus (Journal of Islamic Law)
The times are increasingly demanding more competition in the realm of work which requires the role of women to take part in the competition. The development of the times also has implications for increasing gender equality between men and women and improving the status of career women has spread evenly to the rural corner to help the family economy. This phenomenon makes modern Islamic thinkers try hard to explore legal products that support gender equality, including legal products on contextual interpretations in the form of equalizing the inheritance between men and women. However, these regulations are considered contrary to the rules of the larger in the Islamic Shari'a, which is the argument of the texts of the Koran on the male part and female 2:1. The results showed that the male and female heirs could not be equalized, but instead remained on the rule of 2:1. The results of this study are based on a historical study of the increase in the existence of women who had existed during the revelation, the general provisions in the Shari'a regarding the inheritance of men and women 2:1, and the continuing obligation to provide for the livelihoods charged to men following the nature of their creation. An alternative that allows applying the product of the contextual interpretation of the equalization of the assets of men and women is the distribution of the property of the gono-gini which is shared equally between husband and wife, and then the inheritance of the deceased person to the heirs according to their share.